Comprehensive study of phenolic profile and biochemical activity of monovarietal red and white wines from Fruška Gora region, Serbia - Pintać Šarac, Diandra; Torović, Ljilja; Orčić, Dejan; Mimica-Dukić, Neda; Đorđević, Tatjana; Lesjak, Marija (Food chemistry, 2024)
•Red wines had up to 60 times higher levels of phenolic compounds than white wines.•Hydroxycinnamic acids were a characteristic of white wines.•Anthocyanins were responsible for the highest variations between varieties.•Epicatechin and some phenolic acids could be a terroir characteristic of Fruška Gora.•Domestic and autochthonous Fruška Gora varieties showed great biological potential. This paper presents a comprehensive study of commercially available monovarietal red and white wines from Fruška Gora mountain in Serbia, conducted to characterize their chemical and biochemical properties. Namely, 72 wines of 18 different Vitis vinifera varieties, including international, domestic and autochthonous ones, were assessed. Phenolic profile of wines was determined qualitatively, using spectrophotometric methods, and quantitatively, using LC-MS/MS and HPLC-UV/VIS methods. Quantified phenolic compounds pointed out differences between red and white wines, where some compounds stood out as distinctive characteristic of analyzed varieties, while others served as chemotaxonomic markers of the Fruška Gora region. Antioxidant and inhibitory properties towards acetylcholinesterase were evaluated for all wines and their relation to phenolic composition was investigated. This study is valuable since chemical and biochemical properties of domestic and autochthonous Fruška Gora varieties are reported for the first time. Also, international varieties studied herein gave distinctive information about the terroir of Fruška Gora region, which is scarce in scientific literature.